A split‐face randomized controlled study comparing the efficacy and safety of intralesional radiofrequency‐assisted subcision vs conventional subcision in postacne scars. (31st March 2020) - Kaur, Maninder; Sharma, Vinod K.; Sethuraman, Gomathy; Arava, Sudheer; Gupta, Somesh
Abstract: Background: Postacne scars have significant psychosocial distress among patients. Subcision is a well‐known treatment modality specially for rolling type of acne scars, but is a crude mechanical process, which carries a risk of hematoma formation. Aims: To compare the efficacy and safety of radiofrequency‐assisted subcision (rSubcision) with conventional subcision in postacne scars. Methods: In this randomized, split‐face study, adult patients with postacne scars were randomized to receive either conventional subcision or rSubcision in 2 sessions, 4 weeks apart and followed up for 2 months. Outcome was measured using Goodman and Baron score (GBS), investigator global assessment (IGA) by two blinded dermatologists, and patient global assessment (PGA). Results: Seventeen out of 21 patients completed the treatment. Statistical analysis of the results was performed using SPSS 15.0 statistical software (SPSS). Patients in both the groups had significant improvement from baseline according to quantitative scoring ( P  = .0001), number of scars ( P  = .0001), IGA, and PGA. The improvement was comparable in both the groups according to GBS and IGA but better on rSubcision side in terms of PGA. Two patients developed small entry point burn during rSubcision which healed in one month and one developed persistent hematoma with conventional subcision. Conclusions: Both modalities were comparable in terms of assessment scores and investigator assessment, but patients found improvement better on rSubcision side.